PTU-015 Conversion of colonoscopy requests to flexible sigmoidoscopy: investigating an unknown quantity. (22nd June 2015) - Thompson, C; Walt, R; Ismail, T; Ward, S
Abstract : Introduction: Colonoscopy completion is a key performance indicator and is subject to a Joint Advisory Group standard of 90% in the UK. 1 Inappropriate colonoscopy requests may be as high as 29%. 2 It may be appropriate to convert a colonoscopy to a flexible sigmoidoscopy prior to the procedure to reduce procedure risk. 3 There are no published data indicating how often such conversion occurs. Method: The database of the Unisoft GI reporting tool (Unisoft Medical Systems, UK) was used to identify all patients who underwent a flexible sigmoidoscopy between January 2013 and October 2014 at a large University teaching hospital. Request forms and relevant endoscopy lists were retrieved from hospital electronic records to identify which sigmoidoscopies had been requested and listed as colonoscopies. Endoscopy reports were retrieved to determine reasons given for conversion to sigmoidoscopy. Colonoscopy completion rates for individuals were calculated over the same time period – unadjusted and adjusted so that the denominator included sigmoidoscopies that were requested or booked as colonoscopies. Results: 3619 flexible sigmoidoscopies were performed over the given time period. Request forms were available for 2401 cases (66%) and an entry on a planned endoscopy list was found for 2861 cases (79%). 113 of the 2401 sigmoidoscopies performed (4.7%) had been requested as colonoscopies and 180 of the 2861 listed had been listed as colonoscopies (6.3%). Conversion reason was found in the report in only 22% cases. These were poor prep (8 cases), patient not taken prep (4 cases), poor indication (4 cases), patient choice (3 cases), stricture (3 cases), medically unfit (2 cases), unresolved loop (2 cases) and unable to cannulate (1 case). Conversion rate varied by individual. A funnel plot of conversion rates with 95% boundaries demonstrated 3 individuals with outlying conversion rates. Including conversions caused completion rates to change by between 0 to 8.4% (median 1.7%). Conclusion: A significant number of colonoscopy requests are converted to flexible sigmoidoscopy. The reason for conversion was infrequently cited in the procedure report. When a colonoscopy is converted to a sigmoidoscopy, a clear reason for this must be given in the report. The frequency of conversion in an endoscopy unit should be audited as it has important repercussions on planning, resource allocations and patient experience. It also has the potential to impact on an individual's colonoscopy completion rate. Disclosure of interest: None Declared. References: Valori R, Barton R. BSG Quality & Safety Indicators for Endoscopy. JAG, 2007 Petruzziello L, Hassan C, Alvaro D. J Clin Gastroenterol. 2012;46:590–4 Gatto NM, Frucht H, Sundararajan V, et al . JCNI 2002;95:230–6